Protein expression of ATP-binding cassette transporters ABCC10 and ABCC11 associates with survival of colorectal cancer patients - Krizkova, V; Dubova, M; Susova, S; Vycital, O; Bruha, J; Skala, M; Liska, V; Daum, O; Soucek, P (Cancer chemotherapy and pharmacology, 2016)
PURPOSE: This study investigated the prognostic importance of protein expression of ATP-binding cassette (ABC) transporters ABCC10 and ABCC11 in colorectal cancer. METHODS: Protein content of ABCC10 and ABCC11 was assessed in tumor tissue blocks of 140 colorectal cancer patients and associated with survival of patients with regard to 5-fluorouracil-based therapy. RESULTS: Low ABCC10 protein content in tumors increased hazard ratio of patient's death more than three times in comparison with high ABCC10-expressing tumors (P = 0.004). In contrast, the low ABCC11 content increased the hazard ratio of cancer recurrence in patients almost four times (P = 0.016). Analysis of patients treated with regimens based on 5-fluorouracil revealed that patients with low ABCC11 content in their tumors had shorter disease-free interval than those with higher content (P = 0.024). CONCLUSIONS: The present study shows for the first time that the protein expression of ABCC10 significantly associates with overall survival and the expression of ABCC11 with disease-free interval of colorectal cancer patients and provides strong impulse for further validation of their prognostic value in colorectal cancer.
Keywords: Prognosis; ATP-Binding Cassette Transporters; přežití bez známek nemoci; Disease-Free Survival; retrospektivní studie; Humans; fluoruracil; následné studie; Antimetabolites, Antineoplastic; lokální recidiva nádoru; lidé středního věku; Middle Aged; míra přežití; ABC transportéry; prognóza; Follow-Up Studies; mužské pohlaví; Immunohistochemistry; Neoplasm Recurrence, Local; Survival Rate; Protein; Multidrug Resistance-Associated Proteins; ženské pohlaví; Colorectal cancer; kolorektální nádory; lidé; protinádorové antimetabolity; Fluorouracil; Aged; senioři; Male; Retrospective Studies; Colorectal Neoplasms; proteiny spojené s mnohočetnou rezistencí k lékům; Female